Kinetics of hexene-1 polymerization using [(N,N `-diisopropylbenzene)-2,3-(1,8-napthyl)-1,4-diazabutadiene] dibromonickel/methylaluminoxane catalyst system - Subramanyam, Ummadisetty; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2007)
{Kinetics of hexene-1 polymerization was investigated using [(N,N'-diiso-propylbenzene)2,3-(1,8-napthly)-1,4-diazabutadiene]/dibro monickel/methylaluminoxane catalyst. Experiments were performed at varying catalyst and monomer concentrations in the temperature range of -10 to 35 degrees C. First order time-conversion plot shows a downward curvature at temperatures of 20 degrees C and 35 degrees C indicating the presence of finite termination reactions. A nonlinear plot of degree of polymerization (P-n) with respect to conversion indicates occurrence of transfer reactions and slow initiation. The experimental molar masses are higher than predicted, which implies that a fraction of catalyst species could not be activated or is deactivated at the early stages of the reactions. The efficiency of the catalyst (Cat(eff)) varies from 0.77 to 0.89. The observed polydispersity of the poly(hexene-1) s is in the range of 1.18-1.48. The reaction order was found to be 1.11 with respect to catalyst. The Arrhenius plot obtained using the overall propagation rate constant, k(p), at five different temperatures (-10, 0, 10, 20, and 35 degrees C) was found to be linear with an activation energy
Keywords: Activation energy; chain transfer; degree of polymerization; hexene-1; kinetics (polym.); nickel (alpha-diimine)

Synthesis and characterization of poly(higher-alpha-olefin)s with a nickel(alpha-diimine)/methylaluminoxane catalyst system: effect of chain running on the polymer properties - Subramanyam, Ummadisetty; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2007)
Homopolymerization of octadecene-1 at different reaction conditions has been studied. Significant chain running can be seen at higher polymerization temperatures. Interestingly, insertion of octadecene-1 into a sterically hindered nickel-cation/carbon (secondary) bond is observed. The microstructure of the polymer was established using NMR spectroscopy. The effects of chain running on polymer melting, crystallization behavior, and dynamic mechanical thermal properties were studied using DSC and DMTA. The extent of chain running (i.e., 2 omega-, 1,omega-enchainments) decreases with an increase in the carbon number of alpha-olefins. (c) 2006 Wiley Periodicals, Inc.
Keywords: chain running; Crystallization; glass transition; melt transition; nickel (alpha-diimine); NMR; poly(alpha-olefin)s